Media Pembelajaran PAI dan Budi Pekerti Dalam Kurikulum Merdeka Belajar - Mad Sa’i; Rihatul Jinan (UIN Sunan Gunung Djati Bandung, 2022)
The Independent Learning Curriculum is a curriculum that was initiated to create a happy school and give freedom to students. This freedom of learning is applied because there are many problems regarding the existing national education system as a benchmark in learning. Freedom to learn is a form of policy improvement in increasing the essence of the lost assessment. The concept of independent learning is to improve the national education system that is adapted to the essence of the law in providing school independence by interpreting the basic competencies of the curriculum into their assessment. In implementing it, it is necessary to support appropriate learning media, especially for PAI and Good Manners subjects. The focus of this research is first, what are the learning media for PAI and good manners in the independent learning curriculum. Second, what are the constraints and solutions for learning media when applied to the independent learning curriculum. This type of research uses library research. The data collection technique used in this study is to identify from journal articles, books, and other sources related to these problems. The design of this research is as follows: choosing a topic of discussion, exploring information, choosing a research focus based on information data, examining sources of data or information that has been obtained from various sources, understanding library sources, making research notes, processing research notes and preparing reports. The results of this study First, the media in PAI learning is diverse but there are several media that are easier for educators and students to understand. Second, the obstacle is that the teacher's insight is lacking in mastery of learning media. Less economical learning media, students are less cooperative with various learning media. While the solution is PAI teachers and good manners have to attend a lot of training related to making PABP learning media that is economical, creative. Teachers are able to collaborate with students' parents so that the business of making learning media can run smoothly.